Oxidative stress and antioxidant defences generated by solar UV in a Subantarctic marine phytoflagellate - Pablo Hernando, Marcelo; Malanga, Gabriela Fabiana; Ferreyra, Gustavo Adolfo (Scientia Marina, 2005)
The reduction of the Antarctic stratospheric ozone resulted in significant increases in ultraviolet B radiation (UV-B, 280-320 nm) reaching the surface of the ocean. The main objective of this work was to study long-term (growth rate scale, days) stress responses (lipid oxidative damage, TBARS, and lipid soluble antioxidants) to UV-B and UV-A of a phytoflagellate species (Asteromonas sp.) isolated from a natural phytoplankton community of the Subantarctic Beagle Channel. The growth rate was inhibited by UV-B and UV-A radiation during the exponential phase. A marked increase in the TBARS content was observed on day 1 of the experiment, with significant differences between algae subjected to UV-B and UV-A treatments, thus suggesting high damage to the cell membrane. During the second day of the experiment TBARS in UV-A treatments were higher than under photosynthetically active radiation (PAR). The concentration of TBARS decreased to the level of the PAR control on day 3, remaining low until the end of the experiment. Lipid antioxidant concentrations (?-tocopherol and ?-carotene) were delayed with respect to variations in TBARS, showing maximum values on day 3 of the experiment. This coincided with the minimum TBARS concentrations in all treatments. The content of both antioxidants increased significantly in cultures exposed to UV-B and UV-A on days 3 and 4. In Antarctic species (phytoflagellate Asteromonas sp., AP and diatom Thalassiosira sp., AT) a-tocopherol was more abundant than b-carotene. The phytoflagellate species showed a lag in reaching the maximum content of both antioxidants in relation to AT, which reached the maximum concentration within a short time scale (3 h) suggesting a more rapid response to oxidative stress. AT was more resistant to UVR stress than the phytoflagellate species. Overall, our results show that UVR damage/repair balance involves the combined action of several internal factors in the cell.